Ta-nong - Pucay, John (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
The unnamed narrator relies on his memories as a carefree twelve-year-old to conduct an indigenous spiritual cleansing ritual for his foreign-returned cousin, who requested the ritual for mysterious reasons